HUBUNGAN KECEMASAN DENGAN GANGGUAN POLA TIDUR PADA PASIEN PRE OPERASI FRAKTUR FEMURDI RSUD PROF. DR. SOEKANDAR MOJOSARIKABUPATEN MOJOKERTO - Dwi w, Binarti; Wahyu Handayani, Elita (JURNAL KEPERAWATAN SEHAT, 2012)
ABSTRACTFractures are any cracks or fractures in the bone intact. Femoral fracture pre operative patients typically need assistance in accepting the changes in body image, decreased sense of self, or the inability to perform his obligations in the role. Excessive anxiety is a problem.The sampling method was consecutive sampling. This study purposes to determine the relationship of anxiety with disorders of sleep patterns in femur fracture preoperative patients in of Prof. Dr. Soekandar hospitals Mojokerto. This study is a correlational study with cross sectional approach. The population was all preoperative patients femoral fracture. The results were obtained from 15 respondents found that as many as 12 people (80%) experienced anxiety, and as many as 3 people (20%) did not experience anxiety. While the number and percentage of respondents who experienced a disorders of sleep patterns as many as 11 people (73%), and as many as 4 people (27%), thre is no responden experience a disorders of sleep patterns. Analysis results showed the relationship of anxiety and sleep pattern disturbance levels with non-parametric statistical test Chi Square at significance level α = 0.05 showed a significant association with Pvalue= 0.009 (<α = 0.05). It can be seen that the preoperative femoral fracture patients experience anxiety due to worry with experience physical changes as well as threatening to his role in life, if the femur fracture pre operative patient experienced of anxiety, one may increase the sympathetic nerve that can cause sleep disturbances infrequency.Keywords: Anxiety, sleep disorders, fractures of the femur